Mechanical twinning and dislocation slip multilayered deformation microstructures in β-type Ti–Mo base alloy. (June 2015) - Min, Xiaohua; Emura, Satoshi; Meng, Fanqiang; Mi, Guangbao; Tsuchiya, Koichi
Abstract : A 10-layer Ti–10Mo–1Fe/Ti–10Mo–3Fe alternating stack material was manufactured by hot-roll bonding and heat treatment. The interfaces between layers could not be detected except for transition region in Fe concentration. However, the interfaces prevented {3 3 2}<1 1 3> twinning in the Ti–10Mo–1Fe region from expanding throughout Ti–10Mo–3Fe region which was deformed by dislocation slips despite having the same crystallographic character. The artificially multilayered twinning/dislocation slip deformation microstructures provide a novel approach for controlling the balance between uniform elongation and yield strength in β-type titanium alloys.